Transposing Islamiyyah schools for effective performance in the 21st century in South-West Nigeria - Abdul-Raheem, Bashir (Ilorin journal of religious studies, 2020)
Change is what is constant, but the failure of Islamiyyah schools to comply with the 21st century imperatives might render their performance obsolete in the nearest future. This may have adverse effects on the preservation and spread of Islam, the goals which they stand to achieve. The purpose of this study is to bring to limelight the extent to which Islamiyyah schools are lagging behind in catching up with the 21st century imperatives. Descriptive research design was adopted because the study intended to describe the situation of Islamiyyah schools vis-à-vis the 21st century imperatives. The study gives full descriptions of the structures of katātib and madrasah arms of Islamiyyah schools, which show that they (the schools) are not in tune with the 21st century imperatives. What constitute the 21st century imperatives are critically analysed. Furthermore, guidelines on how the madrasah can meet up with the 21st century imperatives were explained. The study found that the major obstacle to meeting up with the 21st century imperatives is the mentality or mind-set of “This is how our fathers used to do it”. It concluded that such attitude must change if the twenty-first century imperatives are to be met by the Islamiyyah schools.